Larval fish assemblage recovery: a reflection of environmental change in a large degraded river. Issue 1 (29th July 2014) - Mapes, Robert L.; DuFour, Mark R.; Pritt, Jeremy J.; Mayer, Christine M.
Abstract Estuaries are globally important to fisheries but face many anthropogenic stressors that reduce water quality and degrade benthic habitat. The Maumee River estuary has been degraded by industrial contaminants, high sediment and nutrient loads, channelization and elimination of surrounding wetlands, lessening its value as spawning habitat for fishes of Lake Erie. Regulation and better management practices (BMPs) in the watershed have improved the water quality in this estuary, which should result in a response of the biotic community. We compared recent (2010/2011) larval fish assemblage data to similar data from the 1970s (1976/1977) in order to identify changes due to improved water and habitat quality. Family‐level diversity was greater in recent study years compared to the 1970s and family richness increased from 6 to 10. In addition, the abundance of lithophilic spawning fishes was significantly greater in the recent study years. Increased diversity and family richness were consistent with increased water quality in the Maumee River whereas the observed increase in abundance of lithophilic spawners was consistent with an increase in the amount or quality of benthic habitat used by species in these families for spawning. Better wastewater management and agricultural practices in coastal watersheds can benefit the early life stages of fishes, thus benefitting coastal fisheries. Furthermore, larval fish assemblages may be useful indicators of biological integrity because of their sensitivities to environmental change. Routine sampling of estuarine larval fish assemblages could provide practitioners with insight into ecosystem changes and measure the response of the biotic community to restoration.